Low-grade appendiceal mucinous neoplasm (LAMN) – 3-year endoscopic follow-up underlines benign course of LAMN type 1 - Klag, Thomas; Wehkamp, Jan; Bösmüller, Hans; Falch, Claudius; Johannink, Jonas; Malek, Nisar P.; Kirschniak, Andreas; Goetz, Martin (Zeitschrift für Gastroenterologie, 2017)
Low-grade appendiceal mucinous neoplasms (LAMNs) are neoplastic lesions with potential progression to pseudomyxoma peritonei (PMP). In most cases, diagnosis is made because of suspected acute appendicitis or incidentally by computed tomography (CT). However, incidental diagnosis during colonoscopy is rare. We present the case of a 63-year-old man with a LAMN type 1 lesion, diagnosed at routine colonoscopy for surveillance of ulcerative colitis. Because in earlier surveillance colonoscopies, this lesion was misinterpreted as fecal polution, for the first time, this case describes retrospectively a 3-year endoscopic follow-up of LAMN type 1, underlining the benign course of these kind of lesions compared to type 2 lesions with submucosal infiltration. Even though endoscopy and sonography are not accepted as method of choice to detect LAMN lesions, our case highlights their role regarding diagnosis of small lesions, as CT scan was not able to detect the lesion in our case. Even though LAMNs are rare, awareness of LAMN lesions in routine colonoscopy is favorable as potential progression to PMP can not be ruled out.
Keywords: Koloskopie; LAMN; niedriggradige muzinöse Neoplasie; Mukozele